Adsorption behavior and sensing properties of toxic gas molecules onto PtnBe (n = 5, 7, 10) clusters: A DFT benchmark study. (December 2022) - Kaviani, Sadegh; Piyanzina, Irina I.; Nedopekin, Oleg V.; Tayurskii, Dmitrii A.
Abstract: The adsorption characteristics of some toxic gas molecules (CO, SO, NO, NH3, PH3, CH4, and O3 ) onto Ptn Be (n = 5, 7, 10) cluster were scrutinized using density functional theory (DFT) calculations. Adsorption energy analysis revealed that the adsorption energy value of all gas@Ptn Be complexes decreases with cluster size increasing. It was discovered that CH4 gas molecule is physically adsorbed onto Pt5 Be cluster, whereas other gas molecules are highly chemisorbed. Based on natural bond orbital (NBO) analysis, the maximum charge transfer upon adsorption of gas molecules was observed for SO@Ptn Be complex. The band gap variation in Pt5 Be cluster as a result of adsorption of NO gas molecule was found to be the highest ( − 31.37%). However, much shorter recovery time (9 × 10 −4 s) disclosed that Pt5 Be cluster seems available for monitoring CH4 gas molecule. Finally, quantum theory of atoms in molecules (QTAIM) and electron location function (ELF) analyses illustrated the main presence of electrostatic with partially covalent interactions in the studied complexes. Graphical Abstract: ga1 Highlights: DFT calculations were performed to look into the adsorption of some toxic gas molecules onto Ptn Be (n = 5, 7, 10) clusters. The Pt5 Be cluster is highly sensitive towards NO gas molecule. Medium sensing response and very short recovery time of the Pt5 Be cluster for probing CH4 gas molecule.